2020
DOI: 10.3390/nu12123689
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Pattern and Dietary Energy from Fat Associated with Sarcopenia in Community-Dwelling Older Chinese People: A Cross-Sectional Study in Three Regions of China

Abstract: Associations between dietary patterns (DPs) and sarcopenia remain controversial, and fewer studies have mentioned the relationship between dietary energy composition and sarcopenia. The present cross-sectional study was conducted in three regions of China, to detect the associations between DPs and sarcopenia, and to identify the influencing nutrients. Exploratory factor analysis was conducted for DP identification. Logistic regressions were performed to explore the associations between DPs and sarcopenia. Die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 61 publications
3
19
1
Order By: Relevance
“…Numerous epidemiological studies provide evidence that there is a definite association between regional chronic disease and dietary patterns [ 1 , 2 ]. Therefore, increased attention has been paid to the rational dietary structure and balanced nutrient intake.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Numerous epidemiological studies provide evidence that there is a definite association between regional chronic disease and dietary patterns [ 1 , 2 ]. Therefore, increased attention has been paid to the rational dietary structure and balanced nutrient intake.…”
Section: Introductionmentioning
confidence: 99%
“…Food consumption surveys are fundamental to the analysis of food security, the assessment of diet and nutrient intake and the developing nutrition interventions [ 3 , 4 ]. The food frequency questionnaire (FFQ) is one of the most commonly used assessment tools for diet assessment, which is a better measurement than those obtained using three days weighting method or 24 h dietary recall [ 2 ] and has been extensively used in epidemiological studies [ 1 , 2 , 3 ]. Meanwhile, dietary patterns use the FFQ and food intake data to identify the type of foods that are significant for a disease [ 1 , 2 ] or a specific group of people [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, there was a significant association between lower ORs for sarcopenia prevalence and higher intakes of fat, monounsaturated fatty acids, and polyunsaturated fatty acids (Table 3). The relationship between sarcopenia and fat intake has been controversial, because some previous studies have shown that a dietary pattern with a lower percentage of energy from fat was negatively related to the risk of sarcopenia [43,44], but other studies have shown that greater daily fat intake was positively related with skeletal muscle mass and lower sarcopenia prevalence [45,46]. However, the supplementation of specific fatty acids, such as omega-3 fatty acids, increases muscle mass and physical function in elderly people [47].…”
Section: Discussionmentioning
confidence: 99%